2015
DOI: 10.1007/s00338-015-1273-3
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of coral host–pathogen interactions using a stable GFP-labeled Vibrio coralliilyticus strain

Abstract: The bacterium Vibrio coralliilyticus has been implicated as the causative agent of coral tissue loss diseases (collectively known as white syndromes) at sites across the Indo-Pacific and represents an emerging model pathogen for understanding the mechanisms linking bacterial infection and coral disease. In this study, we used a mini-Tn7 transposon delivery system to chromosomally label a strain of V. coralliilyticus isolated from a white syndrome disease lesion with a green fluorescent protein gene (GFP). We t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
(42 reference statements)
0
9
0
Order By: Relevance
“…Even though a stable association seems more likely when microbes are endosymbiotic, consistently detecting the inoculated bacteria over time in any coral compartment would support the notion of a lasting partnership. Stably labeling cells with fluorescent proteins through genetic engineering as suggested by Pollock et al (2015) would allow to precisely track the probiotic bacteria, as well as the offspring generated from their division.…”
Section: Discussionmentioning
confidence: 99%
“…Even though a stable association seems more likely when microbes are endosymbiotic, consistently detecting the inoculated bacteria over time in any coral compartment would support the notion of a lasting partnership. Stably labeling cells with fluorescent proteins through genetic engineering as suggested by Pollock et al (2015) would allow to precisely track the probiotic bacteria, as well as the offspring generated from their division.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, Vibrio coralliilyticus has been used as a model pathogen to gain insights into the establishement and propagation of coral diseases (Sussman et al, 2008 ; O'Santos et al, 2011 ; Garren et al, 2014 ; Pollock et al, 2015 ). The use of phages to control V. coralliilyticus has been reported recently (Efrony et al, 2007 ; Cohen et al, 2013 ) but if phage therapy is to become a practical approach, fundamental knowledge on pathogen-virus interactions must be investigated in detail to evaluate, on the one hand, the therapeutic potential of the candidate phage and, on the other hand, the suitability of the host for phage therapy.…”
Section: Discussionmentioning
confidence: 99%
“…(⋎-Proteobacteria ) as causative agents of coral bleaching for multiple coral species and in multiple locations (Ushijima et al, 2014 ; reviewed in Mera and Bourne, 2018 ). Vibrio coralliilyticus ( V. coralliilyticus ) has emeregd as an important bacterial pathogen model for understanding the establishement and propagation of coral disease (Sussman et al, 2008 ; O'Santos et al, 2011 ; Garren et al, 2014 ; Pollock et al, 2015 ). Studies have shown that V. coralliilyticus infection is temperature dependent and infects the coral endosymbiont Symbiodinum through the production of proteases that inhibit photosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Even though functional studies of corals exist (Lema et al, 2015;Pollock et al, 2015), a laboratory model is needed in order to conduct more elaborate studies, such as experimental replacement of native bacteria in order to assess functional contribution of a specific bacterial species. For this type of experiment, it is essential to obtain bacterial cultivates that represent key microbial symbionts.…”
Section: Cultured Isolates Of Aiptasia-associated Bacteria-toward Funmentioning
confidence: 99%